Intrinsic Differences between Oral and Skin Keratinocytes - Turabelidze, Anna (Public Library of Science, 2014)
Keratinocytes cover both the skin and some oral mucosa, but the morphology of each tissue and the behavior of the keratinocytes from these two sites are different. One significant dissimilarity between the two sites is the response to injury. Oral mucosal wounds heal faster and with less inflammation than equivalent cutaneous wounds. We hypothesized that oral and skin keratinocytes might have intrinsic differences at baseline as well as in the response to injury, and that such differences would be reflected in gene expression profiles.